2022
DOI: 10.5935/1984-0063.20220004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of L-carnitine in narcolepsy treatment: a systematic review on the effectiveness and safety

Abstract: Introduction:Studies have shown that narcolepsy patients may present with low serum acylcarnitine levels, demonstrating a dysfunctional beta fatty acid oxidation pathway in these patients. Objective: Evaluate the therapeutic efficacy of L-carnitine as a treatment for narcolepsy patients. Methods: This study runned in form of systematic review. The terms used for the search: ("narcolepsy"[MeSH Terms] OR "narcolepsy"[All Fields]) AND ("carnitine"[MeSH Terms] OR "carnitine"[All Fields] OR "l carnitine"[All Fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…56 Cataplexy Strong Low improvement of symptoms after treatment with L-carnitine at the onset of symptoms, including pregnancy, in a systematic review. 66,67 Authors observed that the therapeutic efficacy of L-carnitine as a treatment for patients with narcolepsy in a population of 31 patients showed improvement in EDS. 68 Other authors have shown symptomatic improvement after using prednisone and immunoglobulin.…”
Section: Treatmentmentioning
confidence: 99%
“…56 Cataplexy Strong Low improvement of symptoms after treatment with L-carnitine at the onset of symptoms, including pregnancy, in a systematic review. 66,67 Authors observed that the therapeutic efficacy of L-carnitine as a treatment for patients with narcolepsy in a population of 31 patients showed improvement in EDS. 68 Other authors have shown symptomatic improvement after using prednisone and immunoglobulin.…”
Section: Treatmentmentioning
confidence: 99%
“… 71 Furthermore, a recent systematic review found that carnitine supplementation was well tolerated, without side effects, and had some efficacy as a pharmacologic therapy for patients with narcolepsy. 72 This may be a particularly attractive option that is relatively benign compared to other pharmaceutical alternatives for hypersomnia in very young patients with PWS. To be sure, this is an area worthy of further investigation.…”
Section: Hypersomnia and Narcolepsymentioning
confidence: 99%